Single-molecule detection at high concentrations with optical aperture nanoantennas. Issue 18 (27th April 2016) - Alam, Md Shah; Karim, Farzia; Zhao, Chenglong
Abstract : Enhanced single-molecule detection at high concentrations with optical aperture nanoantennas (OANs) is reported. Abstract : Single-molecule detection has become an indispensable technology in life science, and medical research. In order to get meaningful information on many biological processes, single-molecule analysis is required in micro-molar concentrations. At such high concentrations, it is very challenging to isolate a single molecule with conventional diffraction-limited optics. Recently, optical aperture nanoantennas (OANs) have emerged as a powerful tool to enhance the single-molecule detection under a physiological environment. The OANs, which consist of nano-scale apertures on a metallic film, have the following unique properties: (1) nanoscale light confinement; (2) enhanced fluorescence emission; (3) tunable radiation pattern; (4) reduced background noise; and (5) massive parallel detection. This review presents the fundamentals, recent developments and future perspectives in this emerging field.